Effects of a vented mouthguard on performance and ventilation in a basketball field setting - Schulze, A.; Kwast, S.; Busse, M. (Journal of Sports Science & Medicine, 2019)
Mouthguards (MG) have possible effects on performance and breathing. Due to the use of MG some studies reported increases in aerobic capacity, or decreases in cardio-respiratory parameters (Bailey et al., 2015; Garner, 2015; Piero et al., 2015). Other studies found no relevant effects (Bourdin et al., 2006; Collares et al., 2014; Golem et al., 2017). However, previous studies are inconsistent with respect to their designs and with regard to the special requirements of team ball sports. For these reasons, we would like to use this letter to the editor to report new results investigating cardiorespiratory parameters without and with a mouthguard measured in a highly specific basketball course.